In Situ Electrochemical Activation of Atomic Layer Deposition Coated MoS2 Basal Planes for Efficient Hydrogen Evolution Reaction. (2nd August 2017) - Kim, Youngmin; Jackson, David H. K.; Lee, Daewon; Choi, Min; Kim, Tae‐Wan; Jeong, Soon‐Yong; Chae, Ho‐Jeong; Kim, Hyun Woo; Park, Noejung; Chang, Hyunju; Kuech, Thomas F.; Kim, Hyung Ju
Abstract : Molybdenum disulfide (MoS2 ), which is composed of active edge sites and a catalytically inert basal plane, is a promising catalyst to replace the state‐of‐the‐art Pt for electrochemically catalyzing hydrogen evolution reaction (HER). Because the basal plane consists of the majority of the MoS2 bulk materials, activation of basal plane sites is an important challenge to further enhance HER performance. Here, an in situ electrochemical activation process of the MoS2 basal planes by using the atomic layer deposition (ALD) technique to improve the HER performance of commercial bulk MoS2 is first demonstrated. The ALD technique is used to form islands of titanium dioxide (TiO2 ) on the surface of the MoS2 basal plane. The coated TiO2 on the MoS2 surface (ALD(TiO2 )‐MoS2 ) is then leached out using an in situ electrochemical activation method, producing highly localized surface distortions on the MoS2 basal plane. The MoS2 catalysts with activated basal plane surfaces (ALD(Act.)‐MoS2 ) have dramatically enhanced HER kinetics, resulting from more favorable hydrogen‐binding. Abstract : The catalytically inert basal plane of MoS2 is activated for the hydrogen evolution reaction (HER) by combining the atomic layer deposition (ALD) technique and an in situ electrochemical activation process. The basal plane activated MoS2 (ALD(Act.)‐MoS2 ) catalysts significantly improve the HER performance, resulting from more favorable hydrogen‐binding.